2021
DOI: 10.3389/fcell.2021.726656
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Claudin-6 as a Molecular Biomarker in Pan-Cancer Through Multiple Omics Integrative Analysis

Abstract: Claudin-6 (CLDN6) is one of the 27 family members of claudins and majorly involved in the tight junction and cell-to-cell adhesion of epithelial cell sheets, playing a significant role in cancer initiation and progression. To provide a more systematic and comprehensive dimension of identifying the diverse significance of CLDN6 in a variety of malignant tumors, we explored CLDN6 through multiple omics data integrative analysis, including gene expression level in pan-cancer and comparison of CLDN6 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…CLDN6 is an ideal target for antibody approaches of high potency in cancers with high CLDN6 expression based on the fact that CLDN6 is undetectable in the adult tissues [ 24 , 25 , 26 ]. Notably, CLDN6 exerts carcinogenic or anti–carcinogenic effects depending on the tissue or cell type [ 27 ]. As for proliferation, CLDN6 promotes cell proliferation in human hepatocellular carcinoma, gastric cancer, and endometrial carcinoma [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…CLDN6 is an ideal target for antibody approaches of high potency in cancers with high CLDN6 expression based on the fact that CLDN6 is undetectable in the adult tissues [ 24 , 25 , 26 ]. Notably, CLDN6 exerts carcinogenic or anti–carcinogenic effects depending on the tissue or cell type [ 27 ]. As for proliferation, CLDN6 promotes cell proliferation in human hepatocellular carcinoma, gastric cancer, and endometrial carcinoma [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Claudin-6 ( Cldn6 ) is of particular interest, given that changes in gene expression and pathway regulation appeared to be centered around this specific claudin protein. Prior studies suggest claudin-6 is involved in initiating cell adhesion signaling through its role in regulating nuclear receptor gene expression and subsequent activity [ 42 , 43 ]. Expression is predominantly observed in several types of embryonic epithelial cells compared to adult cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Human Protein Atlas (HPA) ( www.proteinatlas.org ) was used to validate the protein levels of MCM2 (HPA031496) based on an immunohistochemistry platform across cancers ( Asplund et al, 2012 ), the transcription level of MCM2 in normal tissues and cell lines and the localization of MCM2. The workflow of this study is shown in Figure 1 ( Wu et al, 2021 ; Zhang et al, 2021a ; Mi et al, 2022 ). We explored the correlations between MCM2 expression and molecular subtypes or immune subtypes across cancers from the TISIDB database ( http://cis.hku.hk/TISIDB ), which integrates multiple data types to assess tumor and immune system interactions ( Ru et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%